Chimeric Contribution of Human Extended Pluripotent Stem Cells to Monkey Embryos Ex Vivo. Issue 7 (July 2021) - Tan, Tao; Wu, Jun; Si, Chenyang; Dai, Shaoxing; Zhang, Youyue; Sun, Nianqin; Zhang, E.; Shao, Honglian; Si, Wei; Yang, Pengpeng; Wang, Hong; Chen, Zhenzhen; et al.
Abstract : (Abstracted from Cell 2021;184:2020–2032) Pluripotent stem cells (PSCs) have demonstrated the ability to be used in interspecies organogenesis through blastocyst complementation, opening the door for production of large quantities of in vivo generated human tissue for regenerative medicine applications. A critical step in this process is the ability of human PSCs (hPSCs) to contribute to chimera formation; however, some studies have shown that hPSCs have little chimeric competency in species evolutionarily distant to humans (eg, mice and pigs).